“Make Believe”: the Images in the Manuscripts of Légende Dorée - Silva Rocha, Tereza Renata (Eikón / Imago, 2017)
This article offers an overview of the visual culture that emerges in the Late Middle Ages, based on new visual patterns. The images of Légende Dorée (c.1348-1500) are within this context, offering us, in general, a rich visual repertoire on the saints. We present the set of codices selected for study and the methodology of its composition, as well as how the images are arranged in relation to the text: the most frequent themes, faded or inspired representations of the text, position of illustrations on the folio among others. We also presented methodological questions about image analysis.